Analysis of the Causes of Failure and Damage to Conveyor Scraper for Transporting Oil Palm Bunches at PT. Socfindo Seunagan Plantation using the FMEA Method (Failure Modes Effect Analysis) - Rizwan; Joli Supardi Joli; Masykur; Veranita (LPPM Politeknik Aceh Selatan, 2023)
PT. Socfindo Kebun seunagan is a company engaged in the plantation and processing of Fresh Fruit Bunches (FFB) into Crude Palm Oil (CPO). Fresh Fruit Bunches before processing, are first transported using a conveyor to be processed into oil (CPO) from a sterilizer. Based on the analysis of damage and failure that often occurs in scrapper conveyor parts, damage is hampered by the productivity of the company. The purpose of this study is to analyze the causes of failure and damage that occur on the scrapper conveyor by calculating the RPN (Risk Priority Number) value of each failure and damage that occurs to determine maintenance actions that need to be followed up. The results of the analysis showed that there were failures and potential damage to the scrapper conveyor, including the release of the scrapper conveyor chain connecting of 135 RPN, the wear of the scrapper conveyor chain of 40 RPN, and the rupture of the bearing of 56 RPN. Connecting the scrapper conveyor chain is more often damaged than other parts, so monitoring and repair are prioritized. Overall, the factors causing damage and failure are caused by lack of routine maintenance so that they are damaged.